Fused Nickel(II) Porphyrins—Sensing of Toxic Anions and Selected Metal Ions Through Supramolecular Interactions - Dar, Tawseef Ahmad; Sankar, Muniappan (Frontiers in Chemistry, 2020)
Ni(II) Porphyrins having fused –NH groups have been synthesized and characterized by various spectroscopic techniques. The synthesized porphyrins 1 and 2 were used to detect species of opposite polarity. Whereas 1 was used to sense toxic anions viz. cyanide and fluoride ions, 2 was used for detecting some selective metal ions including toxic mercury(II) ions. 1 having acidic –NH protons detects anions via hydrogen bonding interactions which leads to deprotonation. On the other hand, 2 senses the metal species via weak charge transfer interactions from oxygen atom of the formyl group to the transition metal ions. The detection limit in case of 1 was found to be 2.13 ppm and 3.15 ppm for cyanide and fluoride ions, respectively. Similarly, the detection limit was found to be 0.930 ppm, 2.231 ppm and 0.718 ppm for Cu(II), Fe(III) and Hg(II) ions, respectively for probe 2. The probes were recovered and reused for several cycles.